IMPLEMENTASI PEMBELAJARAN BERBASIS APLIKASI ZYRA DALAM MENINGKATKAN KEMAMPUAN MINAT DAN MOTIVASI BELAJAR MATEMATIKA - Salsabilla, Fany Hanum; Badruttamam, Alayk Hikam; Andini, Nanda Meilia; Hasanah, Fatmawati Nur (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2025)
ABSTRACT The rapid advancement of educational technology demands innovative learning media that can enhance students’ interest, motivation, and understanding, making interactive tools such as the Zyra application essential for addressing the challenges of learning mathematics in the digital era. This study aims to examine the effectiveness of the Zyra application in increasing students’ interest, motivation, and learning outcomes in mathematics at SD Muhammadiyah 04 Comal. The research employed a qualitative approach using a case study method, in which data were collected through observation, interviews with the application-developing teacher, and analysis of students’ learning outcomes before and after using the Zyra application. Zyra was designed as an interactive Android-based learning media featuring a learning objectives menu, instructional material, educational games, and Augmented Reality (AR) technology for visualizing three-dimensional geometric shapes. The findings indicate that the implementation of the Zyra application had a significant positive impact on students’ interest and learning outcomes. Prior to using the application, students struggled to visualize three-dimensional geometry concepts; however, after using the AR feature in Zyra, their understanding improved significantly. Additionally, the “learning by playing” strategy successfully created a fun and interactive learning environment, leading to greater student motivation. The urgency of this study lies in the need to integrate technology into education to meet the challenges of 21st-century learning, while also serving as inspiration for the development of similar educational applications in the future. ABSTRAK Perkembangan teknologi pendidikan menuntut inovasi pembelajaran yang mampu meningkatkan minat, motivasi, dan pemahaman siswa, sehingga diperlukan media interaktif seperti aplikasi Zyra untuk menjawab tantangan pembelajaran matematika di era digital. Penelitian ini bertujuan untuk mengkaji efektivitas implementasi aplikasi Zyra dalam meningkatkan minat, motivasi, dan hasil belajar siswa pada mata pelajaran matematika di SD Muhammadiyah 04 Comal. Metode penelitian dilakukan melalui pendekatan kualitatif dengan studi kasus, di mana data dikumpulkan melalui observasi, wawancara dengan narasumber (guru pengembang aplikasi), serta analisis dokumen hasil belajar siswa sebelum dan sesudah menggunakan aplikasi Zyra. Aplikasi Zyra dirancang sebagai media pembelajaran interaktif berbasis Android yang mencakup fitur seperti menu tujuan pembelajaran, materi, permainan edukatif, dan teknologi Augmented Reality (AR) untuk visualisasi bangun ruang sisi datar. Hasil penelitian menunjukkan bahwa implementasi aplikasi Zyra memberikan dampak positif signifikan terhadap minat dan hasil belajar siswa. Sebelum menggunakan aplikasi, siswa kesulitan memvisualisasikan konsep geometri tiga dimensi, namun setelah menggunakan fitur AR di aplikasi Zyra, pemahaman mereka meningkat drastis. Selain itu, strategi “learning by playing” berhasil menciptakan lingkungan belajar yang menyenangkan dan interaktif, sehingga siswa lebih termotivasi. Urgensi penelitian ini terletak pada kebutuhan untuk mengintegrasikan teknologi dalam pembelajaran guna menjawab tantangan pendidikan abad 21, serta memberikan inspirasi bagi pengembangan aplikasi serupa di masa mendatang.